Uptown/downtown in old Charleston : sketches and stories - Rubin, Louis D., Jr. (Louis Decimus), 1923-2013 (University of South Carolina Press, 2010)
A series of briskly paced renderings of the Holy City's dual identities, written by an acclaimed native son.